Non-occlusive mesenteric ischaemia: The prevalent cause of gastrointestinal infarction in patients with severe burn injuries. Issue 1 (January 2015) - Muschitz, Gabriela K.; Fochtmann, Alexandra; Keck, Maike; Ihra, Gerald C.; Mittlböck, Martina; Lang, Susanna; Schindl, Martin; Rath, Thomas
Abstract: Background: Gastrointestinal complications occur frequently in intensive care patients with severe burns. Intestinal infarction and its deleterious consequences result in high mortality despite rapid surgical intervention. Our objective was to evaluate the aetiology of gastrointestinal infarction in intensive care patients with severe burns. Study design: We retrospectively evaluated all of the severe-burn victims at the burn unit of the Medical University of Vienna from 01/2002 to 06/2012 for whom a gastrointestinal infarction was diagnosed during their inpatient stay on computed-tomography, in the context of acute laparotomy, or upon autopsy by aetiology. Results: After a severe thermal injury, 17 patients suffered a gastrointestinal infarction during their stay. In 82% of those patients, non-occlusive mesenteric ischaemia (NOMI) was identified as the cause of the gastrointestinal infarction. Patients with an embolic infarction tended to be older (78.0 years embolism vs. 53.4 NOMI, mean, p < 0.01), with a lower abbreviated burn severity index (8.7 embolism vs. 10.4 NOMI, mean, p < 0.02) and a smaller total body surface area burned (20% embolism vs. 48% NOMI, mean, p < 0.01) than those with a non-occlusive mesenterial ischaemia. No patients with an embolic infarction or any of the females in the entire gastrointestinal infarction group survived this event, resulting in a mortality rate of 100% for the embolic infarction group and female group. The decisive factor for surviving a NOMI was age (median age: male survivors 28 years vs. nonsurvivors 66 years (of this median, males = 72 years and females = 60 years), p < 0.02). Conclusion: The results of our study clearly demonstrate that in severe-burn intensive care patients, non-occlusive mesenteric ischaemia is the most frequent cause of gastrointestinal infarction and that the decisive factor for survival is the patient's age.